2012
DOI: 10.1108/09654281211253425
|View full text |Cite
|
Sign up to set email alerts
|

How do Australian junior primary school children perceive the concepts of “healthy” and “unhealthy”?

Abstract: PurposeThis paper aims to describe Australian children's perceptions of healthiness and sources of health knowledge in order to develop an understanding of young children's perceptions, knowledge and sources of influence to guide future behaviour change and health promotion strategies.Design/methodology/approachOne‐hour interactive focus groups were conducted in a South Australian primary school. Four small groups (n=28) of children aged five to nine participated in focus groups in which they were asked to dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…Studies examining children's decisions about what is 'healthy' and 'less healthy' reveal complex relationships between diet and health (Dixey et al 2001), and diet and physical activity (Brindal et al 2012). Children understand healthy eating and have a high awareness of food 'healthiness' (Dixey et al 2001;Hesketh et al 2005;O'Dea 2003;Protudjer et al 2010), particularly of whole foods and ingredients (Thompson et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Studies examining children's decisions about what is 'healthy' and 'less healthy' reveal complex relationships between diet and health (Dixey et al 2001), and diet and physical activity (Brindal et al 2012). Children understand healthy eating and have a high awareness of food 'healthiness' (Dixey et al 2001;Hesketh et al 2005;O'Dea 2003;Protudjer et al 2010), particularly of whole foods and ingredients (Thompson et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…The influence of parent–child interactions on healthy diet is strongest when children are aged 5–11 years old (Cislak et al, 2012). Previous research indicated that children as young as 5–9 years old perceive their parents as the primary source of nutrition information (Brindal, Hendrie, Thompson, & Blunden, 2012). During the adolescence period, parental influence decreases while peers and media start to play a significant role in shaping adolescents’ beliefs and behaviors (Cislak et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research investigating children's perception of healthy food environment indicated that those who are 5-9 years old perceive their parents and mass media as the primary source of nutrition information [17]. Thus, at-home availability of healthy food and perceptions of food advertising have been investigated in children as young as 5-9 years old [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research investigating children's perception of healthy food environment indicated that those who are 5-9 years old perceive their parents and mass media as the primary source of nutrition information [17]. Thus, at-home availability of healthy food and perceptions of food advertising have been investigated in children as young as 5-9 years old [17,18]. Although teachers are reported by children as the source of information on healthy food, qualitative research did not elicit perceptions of programs at local community or at the school setting as relevant sources of information about health or healthy diet among young children [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation